From buffalo to human: Klebsiella pneumoniae in high-somatic cell count milk as an overlooked link in the one health chain - Zhifei Wei; Yifei Xiang; Xuelian Mo; Wenjing Li; Erqiang Wang; Changhua Lin; Jiazhou Wei; Yulian Xi; Yuying Liao; Zhengmin Liang; Zhiran Xu; Jiakang He (International Journal of Food Microbiology, 2026)

Aromatic protein-like recognition enables rapid prediction of sludge deep dewaterability - Jianting Liu; Zhihua Mo; Qingyi Lei; Haowen Guo; Shengye Lin; Zhijian Fu; Jialin Liang; Shuiyu Sun (Bioresource Technology, 2026)

Illicium verum polysaccharide targets fimbriae and flagella to disrupt biofilm and inhibit multidrug-resistant Escherichia coli proliferation - Yifei Xiang; Erqiang Wang; Xuelian Mo; Zhifei Wei; Zhiran Xu; Wenjing Li; Changhua Lin; Yanwen Zhang; Chunxia Ma; Bin Zheng; Ziyang Li; Chengzhi Liu; et al. (Carbohydrate Polymers, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Transforming waste copper slag into a nitrogen-doped mesoporous catalyst for singlet oxygen-dominated peroxymonosulfate activation toward efficient and sustainable degradation of rhodamine B - Ying Zhang; Chunjie Huang; Ying Lin; Xingyong Xue; Lihong Lan; Yaocong Han; Qiaoqiao Su; Jinlu Liang; Dongping Wei; Linqiang Mo (Environmental Research, 2026)

Synthesis of NiFe-Fc-MOF/LDH/NF with tip effect enhancing electric field for oxygen evolution reactions - Xiangyu Meng; Liang Ma; Zengyan Wei; Jia Song; Fengqi Zhang; Shihao Wu; Mo Yan; Bo Chen; Lin Zhu; Dechang Jia; Yu Zhou; Xiaoming Duan (Chemical Engineering Journal, 2026)

Effects of norgestrel on the reproductive endocrine system, hepatic damage and antioxidant responses of marine medaka (Oryzias melastigma) at different salinities - Jian Song; Chao Zheng; Yan-Qiu Liang; Zhongdian Dong; Chang-Gui Pan; Wen-Jun Shi; Qidan Zheng; Shuhui Zhou; Mingwei He; Xipeng Mo; Zhong Lin (Aquatic Toxicology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Lactiplantibacillus pentosus JWN01 and Lactiplantibacillus plantarum JWN02 attenuate renal fibrosis and pathological autophagy in hyperuricemic nephropathy via gut–kidney axis - Qizhou Mo; Min Qin; Haiqi Liang; Liwei Wei; Yujian Li; Yangmei Qin; Lichun Tang; Jing Liang; Chong Qian; Yilong Liang; Shufeng Luo; Yutuo Wei; et al. (Food Research International, 2026)

A novel potential toxic target of PBDEs in cetaceans: Impaired wound healing demonstrated in Indo-Pacific finless porpoise fibroblasts - Yajing Sun; Chengzhang Li; Ying Zeng; Imran Rashid Rajput; Jiashen Tian; Yuqi Wu; Juntao Ye; Ziyan Wang; Qinghong Liao; Jiezhang Mo; Zonghang Zhang; Jianqing Lin; et al. (Journal of Hazardous Materials, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

The antibacterial activity and metabolomic analysis of the recombinant lectin protein PFL-96 derived from Pinctada fucata against Streptococcus agalactiae isolated from tilapia (Oreochromis niloticus) - Xiaojian Mo; Wenyue Li; Jianbing Liu; Qiting Li; Zhongxiu Liang; Xinyu Liang; Jiaxing Tang; Jiahui Liang; Jiang Lin; Peng Liu (Fish & Shellfish Immunology, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Hierarchical iron phosphides@hard carbon composite cathodes for phenol degradation by highly efficient heterogeneous electro-Fenton - Lizheng Yang; Jiayang Lin; Jiayang Mo; Yingxin Wang; Chenhao Liang; Yanbo Chen; Qilun Huang; Dongying Hu; Xiurong Li (Journal of Cleaner Production, 2025)

Zero-valent Fe and MnSO4 collectively stimulate the degradation-related functionalities in the bacterial secretome affecting the efficient degradation of lignocellulose during composting - Xiaolin Lu; Qiqiang Zhang; Shangyu Lin; Rongchun Huang; Yinfeng Yang; Naiguo Mo; Shasha Liang; Guangsheng Qin; Qunliang Li (Chemical Engineering Journal, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

RNA-binding protein expression based machine learning model predicts metastasis and treatment outcome of testicular cancer - Lin-jian Mo; Hai-qi Liang; Zhen-yuan Yu; Yao-wen Liang; Chuan-xin Gu; Qiu-ju Wei; Qi-huan He; Fa-ye Wei; Ji-wen Cheng; Zeng-nan Mo (Genes & Genomics, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Structural characteristics of global virtual water network driven by food consumption in the Belt and Road Initiative region - Qiumeng Zhong; Jiajing Pan; Zehan Lin; Yumeng Li; Xin Mo; Pan He; Xin Cao; Sai Liang (Resources, Conservation and Recycling, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

Structure-Functional Activity of Pyrone Derivatives for Inhibition of Barnacle Settlement and Biofilm Formation - Mo Aqib Raza Khan; Bo-Wei Wang; Hsiu-Chin Lin; Yu-Liang Yang; Chih-Chuang Liaw (Marine Biotechnology, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

pH-dependent mechanisms of sulfadiazine degradation by natural pyrite-driven heterogeneous Fenton-like reactions - Xiaoxuan Lin; Jinwen Hu; Zhihua Mo; Zhen Wang; Ruyi Wang; Jialin Liang (Journal of Environmental Management, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Differentiation of bone marrow mesenchymal stem cells into Leydig-like cells with testicular extract liquid in vitro - Rong Hua; Fang-Fang Liang; Fang-Qiang Gong; Hua Huang; Yi-Chen Xu; Min He; Yan-Hua Fang; Ya-Shu Wei; Wei-Wei Zhou; Arshad Mehmood; Yi Mo; Zhong Lin (In Vitro Cellular & Developmental Biology - Animal, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Temporal variations of carbon and water fluxes in a subtropical mangrove forest: Insights from a decade-long eddy covariance measurement - Ruikun Gou; Nina Buchmann; Jinshu Chi; Yunpeng Luo; Lidong Mo; Ankit Shekhar; Iris Feigenwinter; Lukas Hörtnagl; Weizhi Lu; Xiaowei Cui; Yuchen Meng; Shanshan Song; et al. (Agricultural and Forest Meteorology, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Physical enrichment for improving welfare in fish aquaculture and fitness of stocking fish: A review of fundamentals, mechanisms and applications - Zonghang Zhang; Wuhan Lin; Yunqi Li; Xianyu Yuan; Xianqing He; Hancheng Zhao; Jiezhang Mo; Jianqing Lin; Liangliang Yang; Bo Liang; Xiumei Zhang; Wenhua Liu (Aquaculture, 2023)

Association of CYP19A1 Gene, Plasma Zinc, and Urinary Zinc with the Risk of Type 2 Diabetes Mellitus in a Chinese Population - Xuexiu Wang; Yujian Liang; Qiumei Liu; Jiansheng Cai; Xu Tang; Shuzhen Liu; Junling Zhang; Min Xu; Chunmei Wei; Xiaoting Mo; Yanfei Wei; Yinxia Lin; et al. (Biological Trace Element Research, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Corrigendum to “Association of serum per- and polyfluoroalkyl substances and gestational anemia during different trimesters in Zhuang ethnic pregnancy women of Guangxi, China” [Chemosphere. Dec 2022 309:136798] - Qian Liao; Peng Tang; Dongxiang Pan; Yanye Song; Lei Lei; Jun Liang; Bihu Liu; Mengrui Lin; Huishen Huang; Meile Mo; Chengtuo Huang; Ming Wei; et al. (Chemosphere, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Three new ester glycosides with cytotoxic activity from the seeds of Caesalpinia sappan - Min Wang; Juan Tan; Jun Chen; Tian Xie; Liang-Mo Lin; Li-Li Zhong; Xing-Jun Cai; Qiong-Shi Wu (Natural Product Research, 2021)

Exogenous Melatonin and Catechol Application Modulate Physio-Biochemical Attributes and Early Growth of Fragrant Rice Under Cd Toxicity - Yuzhan Li; Luxin Liang; Shicong Huang; Wu Li; Umair Ashraf; Lin Ma; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2021)

Natural polyketide 6-pentyl-2 H -pyrone-2-one and its synthetic analogues efficiently prevent marine biofouling - Mo Aqib Raza Khan; Bo-Wei Wang; Yih-Yu Chen; Ting-Hsuan Lin; Hsiu-Chin Lin; Yu-Liang Yang; Ka-Lai Pang; Chih-Chuang Liaw (Biofouling, 2021)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Sorption-desorption behaviors of heavy metals by biochar-compost amendment with different ratios in contaminated wetland soil - Zhaoxue Yang; Jie Liang; Lin Tang; Guangming Zeng; Man Yu; Xiaodong Li; Xuemei Li; Yingying Qian; Haipeng Wu; Yuan Luo; Dan Mo (Journal of Soils and Sediments, 2018)

Sleep medicine in Taiwan - Ning-Hung Chen; Liang-Wen Hang; Chia-Mo Lin (Sleep and Biological Rhythms, 2016)

Down-regulation of the ErbB3 binding protein 1 in human bladder cancer promotes tumor progression and cell proliferation - Hui-chan He; Xiao-hui Ling; Jian-guo Zhu; Xin Fu; Zhao-dong Han; Yu-xian Liang; Ye-han Deng; Zhuo-yuan Lin; Guo Chen; Yan-fei Chen; Ru-jun Mo; Wei-de Zhong (Molecular Biology Reports, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)